MM-183 CARTITUDE-2 Cohort A: Updated Clinical Data and Biological Correlative Analyses of Ciltacabtagene Autoleucel (cilta-cel) in Lenalidomide-Refractory Patients With Progressive Multiple Myeloma (MM) After 1–3 Prior Lines of Therapy (LOT) - Hillengass, Jens; Cohen, Adam D.; Delforge, Michel; Einsele, Hermann; Goldschmidt, Hartmut; Weisel, Katja; Raab, Marc Steffen; Scheid, Christof; Schecter, Jordan M.; de Braganca, Kevin C.; Varsos, Helen; Yeh, Tzu min; et al. (Clinical Lymphoma, Myeloma and Leukemia, 2022)
Context: CARTITUDE-2 (NCT04133636) Cohort A is assessing cilta-cel in lenalidomide-refractory patients with progressive MM after 1–3 prior LOT. Objective: To present updated results from CARTITUDE-2 Cohort A. Design: Phase 2, multicohort study. Patients: Lenalidomide-refractory patients with progressive MM after 1–3 prior LOT (PI and IMiD included) and no previous exposure to BCMA-targeting agents. Interventions: Single cilta-cel infusion (target dose 0.75×106 CAR+ viable T-cells/kg) after lymphodepletion Main Outcome Measures: Primary endpoint was minimal residual disease (MRD) negativity at 10-5. Management strategies were used to reduce risk of movement/neurocognitive adverse events (MNTs). Pharmacokinetics (PK) (Cmax/Tmax of CAR+T-cell transgene levels), cytokine release syndrome (CRS)-related cytokines over time, peak cytokine levels by response/CRS, association of cytokine levels with immune effector cell-associated neurotoxicity syndrome (ICANS), and CAR+T-cell CD4/CD8 ratio by response/CRS/ICANS are being evaluated. Results: As of January 2022 (median follow-up [MFU] 17.1 months), 20 patients (65% male; median age 60 years; median 2 prior LOT; 95% refractory to last LOT) received cilta-cel. Overall response rate was 95% (90% ≥complete response; 95% ≥very good partial response). Median times to first and best response were 1.0 month and 2.6 months, respectively. All 16 MRD-evaluable patients achieved MRD negativity at 10-5. Median duration of response was not reached. At 12 months, event-free rate was 79% and progression-free survival rate was 75%. 95% of patients had CRS (gr3/4 10%); median time to onset was 7 days and median duration was 3 days. Neurotoxicity was reported in 30% of patients (5 gr1/2; 1 gr3/4) and ICANS in 15% (all 3 gr1/2); 1 patient had gr2 facial paralysis. No MNTs were observed. 1 death occurred due to COVID-19 (treatment-related), 2 due to progressive disease, and 1 due to sepsis (not treatment-related). Preliminary PK analyses showed peak CAR-T cell expansion at day 10.5; median persistence was 153.5 days. Conclusions: At MFU of 17.1 months, a single cilta-cel infusion resulted in deep and durable responses in lenalidomide-refractory MM patients with 1–3 prior LOT. We will present updated PK/cytokine/CAR-T subset analyses and clinical correlation to provide novel insights into biological correlates of efficacy/safety in this population.
CRIS-Team Scopus Importer:2023-03-23
Keywords: CAR-T; cilta-cel; MM; multiple myeloma; Phase II